Cosmetics and pregnancy: perception of health risk by health professionals and pregnant women. (13th November 2019) - Sauvant-Rochat, M; Kouamé, N G L; Fradet, M R; Marie, C; Bernard, L; Maquinghen, S; Lémery, D; Vendittelli, F
Abstract: Contex: During pregnancy, the International Federation of Gyneco-Obstetrics (FIGO) advocates limiting exposure to chemicals present in everyday products, including cosmetics. However, both pregnant women (PW) and perinatal health professionals (PHP) know still poorly this source of exposure. AIMS: The PERICOS-Quali Study aims to identify the perception of the risk associated with the use of cosmetics during pregnancy by PHP and PW. Methodology: A qualitative survey was conducted among PHP and PW in Auvergne (France). The data were collected by semi-structured interviews with the PHP and by focus group with the PW, until saturation of the speeches, by an experienced investigator, with an interview guide. The interviews were recorded, the verbatim was transcribed and subjected to a thematic analysis with the N-VIVO v11 software. Results: 12 PHP (5 midwives, 2 general practitioners and 5 obstetricians) and 24 PW were interviewed. PHP and PW considered cosmetics as wellness and body-care products. Furthermore PHP noted that during pregnancy women used more often organic products, moisturizers or anti-stretch marks, and reduced the use of perfumes, deodorants. In the absence of recommandations based on Evidence-Based Medecine, PHP and PW considered the risk related to cosmetics as not major. The PHP (especially midwives) reported giving advice to comfort the pregnant women; their positioning was not to prohibit the use of cosmetics during pregnancy. PW did not identify PHP as reliable sources of information about cosmetics. Conclusions: PHP are seeking for tools to help them to better advice PW. And PW would like also to have pertinent advices about cosmetics to make a reasoned choice. Key messages: Health education about use of cosmetics during pregnancy is necessary. Pregnant women and health professionals don't perceive health risk linked to cosmetics.